Stove Tiles from the Wooden Structure Built on the Ruins of the Medieval Castle of Vrbovec near Hum na Sutli (Archaeologia Adriatica, 2010)
Archaeological excavations have been carried out over a series of years in the northwestern-most part of the Hrvatsko zagorje region, at Hum na Sutli, at a castle whose medieval name was Vrbovec. Burg was mentioned in rare historical sources in the period from the second half of the 13th century to the second half of the 15th century. The excavations have resulted in data about its earlier beginnings, as well as its lengthier continuation, in fact a subsequent utilization if the medieval position in the early modern period, i.e. in the 16th century. The remains of a wooden structure, probably a tower destroyed by fire, were found at the site, built on the ruins of the medieval castle (Fig. 1). On the basis of the width of the foundation pit for this wooden structure, it can be concluded that this was a building constructed of massive wooden beams or the structure had several levels. The remains of a demolished tile stove were also found. The stove was covered with three types of tiles – tiles with a solid front decorative panel depicting a hunting scene (Fig. 2, Pl. 1/1), tiles with a perforated front panel decorated with architectural motifs (Fig. 3, Pl. 1/2), and simple bowl-shaped ties with a square opening (Fig. 4, Pl. 1/3). The first type of tile represents a copy of the kind of tiles that were found at the Celje castle, where they were dated to the last quarter of the 15th century and the transition from the 15th to the 16th centuries. On the basis of the stratigraphy of the finds, the typology of the stove tiles, and radiocarbon analyses, the tile stove from Vrbovec is dated to the second half of the 16th century. Although there is no specific mention of this in the historical sources, the early modern period horizon of the ruins at the medieval castle of Vrbovec should be tied to the aristocratic Rattkay family. The burg Vrbovec at Klenovec Humski with this discovery has become not merely an archaeological source for the medieval period, but also an excellent source for investigating the early modern period.
Keywords: castle; archaeological excavations; stove tiles; late medieval period; early modern period; 16th century; Klenovec Humski; Hrvatsko zagorje (Croatian Highlands)